On paternalistic leadership fit: exploring cross-cultural endorsement, leader-follower fit, and the boundary role of organizational culture - Mansur, Juliana Arcoverde (2016)
Although cross-cultural leadership research has thrived in international business literature, little attention has been devoted to understanding the effectiveness of non-western theories beyond their original contexts. The purpose of this study is to examine the cross-cultural endorsement of paternalistic leadership, an emerging non-western leadership theory, using data from GLOBE project. Using multigroup confirmatory factor analyses we found measurement equivalence of a scale derived from GLOBE’s data, which enabled us to compare the endorsement of paternalistic leadership dimensions across 10 cultural clusters and 55 societies. Our study revealed that there are significant differences in the importance societies give to each dimension, suggesting that paternalism as leadership style is not universally nor homogeneously endorsed. Furthermore, results suggest that different patterns of endorsement of each of these dimensions give rise to idiosyncratic shades of paternalistic leadership across societies. Implications for theory and future research on international business are discussed.